"Hamburg in Motion". Commuting and labour market integration among employees in Hamburg - Kotte, Volker (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
The number of persons commuting to and from work is steadily increasing. In this paper, commuting patterns in the city of Hamburg, Germany, are examined over a period of 13 years. Drawing on unique career data of 730,000 persons who were employed or lived in Hamburg in the year 2000, (1), in-, out-, and non-commuters are compared with regard to labor market outcomes such as employment and unemployment. (2), the rationales for decisions of commuters to relocate their place of residence nearby the workplace are analyzed. It becomes apparent that those who commute to Hamburg are more often employed than those who do not commute. Non-commuters, however, are more successful on the labor market than those who commute from Hamburg to workplaces outside the city so that the benefits of commuting do not outweigh its costs for all types of mobility between residence and workplace. Finally, moving to the workplace region is depending on several personal characteristics. The findings mainly verify the results of existing mobility studies.
Keywords: Commuting; Mobility; Labor market integration; Residential location decision; Hamburg